Introductory and Concluding Text Units for the President’s Special Occasion Speech and Inaugural Speech - Božič Kac, Eva; Krajnc Ivič, Mira (Slavistična prepletanja 6, 2025)
The article analyses 41 speeches delivered by the Presidents of the Republic of Slovenia on special occasions, i.e. on national holidays, and their inauguration speeches. The collected speeches were delivered in the period from the independence of the Republic of Slovenia to 31 December 2023. From the rhetorical point of view, they are epideictic genres and, from the point of view of vertical and horizontal grouping of texts into text groups, they are two independent genres of the text class political speech of the communication field of politics. In Slovenia, the two genres are intertwined, as the inauguration takes place a few days before the national holiday Independence and Unity Day. As epideictic genres, they have a ritual and symbolic function and are part of celebrations in which the speaker praises or discredits a person, a social group, an institution, an event. The intertwining of the two genres is also reflected in their introductory and concluding obligatory or optional text units.